Development and Evaluation of an Enhanced LAMP Primer Set for Detection of Potato Virus Y - Omnia T. Elshorbagy; Adrian Fox; Kirsty J. McInnes; Neil Boonham (Potato Research, 2026)
Whilst molecular methods for plant virus detection are usually based on PCR amplification, loop mediated isothermal amplification (LAMP) is a rapid and sensitive molecular diagnostic tool increasingly used for plant virus detection, particularly in field conditions and resource-limited laboratories. In this study, a novel LAMP primer set (ID: 334) was developed for the specific detection of Potato virus Y (PVY), a globally significant pathogen responsible for yield losses of up to 80% in potatoes. Primer set 334 was designed based on conserved regions identified across 30 complete PVY genomes. It was evaluated against 33 PVY isolates representing 5 strain groups. The assay demonstrated 100% inclusivity, successfully detecting all isolates, including both recombinant and non-recombinant strains. Specificity testing confirmed no cross amplification with related potyviruses (Potato virus A (PVA) and Potato virus V (PVV)) or unrelated potato viruses (Potato virus X (PVX), Potato leafroll virus (PLRV), and Potato mop-top virus (PMTV)), further validating the exclusiveness of the assay. Moreover, the assay was validated on multiple host matrices, including leaves and tuber tissues of potato. Compared to a previously published LAMP assay, primer set 334 exhibited 2.6-fold greater sensitivity, detecting PVY at four orders of magnitude lower concentrations, with performance comparable to qPCR but with faster time-to-result. This improved LAMP assay provides a rapid, specific, and sensitive tool for PVY detection in leaves and tubers, supporting both laboratory, field, and post-harvest diagnostics.

Monitoring root rot in flat-leaf parsley via machine vision by unsupervised multivariate analysis of morphometric and spectral parameters - Avinash Agarwal; Filipe de Jesus Colwell; Julian Bello Rodriguez; Sarah Sommer; Viviana Andrea Correa Galvis; Tom Hill; Neil Boonham; Ankush Prashar (European Journal of Plant Pathology, 2024)
Use of vertical farms is increasing rapidly as it enables year-round crop production, made possible by fully controlled growing environments situated within supply chains. However, intensive planting and high relative humidity make such systems ideal for the proliferation of fungal pathogens. Thus, despite the use of bio-fungicides and enhanced biosecurity measures, contamination of crops does happen, leading to extensive crop loss, necessitating the use of high-throughput monitoring for early detection of infected plants. In the present study, progression of foliar symptoms caused by Pythium irregulare -induced root rot was monitored for flat-leaf parsley grown in an experimental hydroponic vertical farming setup. Structural and spectral changes in plant canopy were recorded non-invasively at regular intervals using a 3D multispectral scanner. Five morphometric and nine spectral features were selected, and different combinations of these features were subjected to multivariate data analysis via principal component analysis to identify temporal trends for early segregation of healthy and infected samples. Combining morphometric and spectral features enabled a clear distinction between healthy and diseased plants at 4–7 days post inoculation (DPI), whereas use of only morphometric or spectral features allowed this at 7–9 DPI. Minimal datasets combining the six most effective features also resulted in effective grouping of healthy and diseased plants at 4–7 DPI. This suggests that selectively combining morphometric and spectral features can enable accurate early identification of infected plants, thus creating the scope for improving high-throughput crop monitoring in vertical farms.

A survey of rose viruses in England - Ines Vazquez-Iglesias; Neil Boonham; Rebekah Robinson; Gerard R.G. Clover; Adrian Fox (Crop Protection, 2023)

High throughput sequencing and RT-qPCR assay reveal the presence of rose cryptic virus-1 in the United Kingdom - Ines Vazquez-Iglesias; Ian Patrick Adams; Jennifer Hodgetts; Aimee Fowkes; Stephen Forde; Richard Ward; Adam Buxton-Kirk; Michael Kelly; Jone Santin-Azcona; Anna Skelton; Valerie Harju; Neil Boonham; et al. (Journal of Plant Pathology, 2019)

Genomic sequence and host range studies reveal considerable variation within the species Arracacha virus B - Roger A. C. Jones; Adrian Fox; Neil Boonham; Ian P. Adams (Archives of Virology, 2019)

Prospects and challenges of environmental DNA (eDNA) monitoring in freshwater ponds - Lynsey R. Harper; Andrew S. Buxton; Helen C. Rees; Kat Bruce; Rein Brys; David Halfmaerten; Daniel S. Read; Hayley V. Watson; Carl D. Sayer; Eleanor P. Jones; Victoria Priestley; Elvira Mächler; et al. (Hydrobiologia, 2019)

The impact of high throughput sequencing on plant health diagnostics - Ian P. Adams; Adrian Fox; Neil Boonham; Sébastien Massart; Kris De Jonghe (European Journal of Plant Pathology, 2018)

Evaluation and validation of a loop-mediated isothermal amplification test kit for detection of Hymenoscyphus fraxineus - Catherine Harrison; Jenny Tomlinson; Sioban Ostoja-Starzewska; Neil Boonham (European Journal of Plant Pathology, 2017)

Complete sequence and genomic annotation of carrot torradovirus 1 - Zuriñe Rozado-Aguirre; Ian Adams; Adrian Fox; Matthew Dickinson; Neil Boonham (Archives of Virology, 2017)

Molecular and biological characterisation of two novel pomo-like viruses associated with potato (Solanum tuberosum) fields in Colombia - Jose Fernando Gil; Ian Adams; Neil Boonham; Steen Lykke Nielsen; Mogens Nicolaisen (Archives of Virology, 2016)

A new quantitative real-time PCR assay for Rhizoctonia solani AG3-PT and the detection of AGs of Rhizoctonia solani associated with potato in soil and tuber samples in Great Britain - James W. Woodhall; Ian P. Adams; Jeff C. Peters; Glyn Harper; Neil Boonham (European Journal of Plant Pathology, 2013)

A new large scale soil DNA extraction procedure and real-time PCR assay for the detection of Sclerotium cepivorum in soil - James W. Woodhall; Kathryn M. Webb; Patricia M. Giltrap; Ian P. Adams; Jeff C. Peters; Giles E. Budge; Neil Boonham (European Journal of Plant Pathology, 2012)

First record of the Q Biotype of the sweetpotato whitefly, Bemisia tabaci, intercepted in the UK - Michelle E. Powell; Andrew G. S. Cuthbertson; Howard A. Bell; Neil Boonham; Jane Morris; Phil Northing (European Journal of Plant Pathology, 2012)

Development of a real-time PCR assay for detection of Phytophthora kernoviae and comparison of this method with a conventional culturing technique - Kelvin J. D. Hughes; Jenny A. Tomlinson; Patricia M. Giltrap; Victoria Barton; Ellie Hobden; Neil Boonham; Charles R. Lane (European Journal of Plant Pathology, 2011)

Exploiting generic platform technologies for the detection and identification of plant pathogens - Neil Boonham; Rachel Glover; Jenny Tomlinson; Rick Mumford (European Journal of Plant Pathology, 2008)

Advances in molecular phytodiagnostics – new solutions for old problems - Rick Mumford; Neil Boonham; Jenny Tomlinson; Ian Barker (European Journal of Plant Pathology, 2007)

Advances in molecular phytodiagnostics – new solutions for old problems - Rick Mumford; Neil Boonham; Jenny Tomlinson; Ian Barker (European Journal of Plant Pathology, 2006)

Host Range Studies for Tomato chlorosis virus, and Cucumber vein yellowing virus Transmitted by Bemisia tabaci (Gennadius) - Jane Morris; Elspeth Steel; Penny Smith; Neil Boonham; Nicola Spence; Ian Barker (European Journal of Plant Pathology, 2006)

Potato Virus Y from Petunia can cause Symptoms of Potato Tuber Necrotic Ringspot Disease (PTNRD) - Neil Boonham; Matthew Hims; Ian Barker; Nicola Spence (European Journal of Plant Pathology, 1999)

The Characterization of a Subgenomic RNA and In Vitro Translation Products of Oat Chlorotic Stunt Virus - Neil Boonham; Christine M. Henry; K. Roger Wood (Virus Genes, 1998)